PENERAPAN STANDAR KOMPETENSI LULUSAN DAN STANDAR ISI DI SMP NEGERI 1 DAWAN - Purnamayathi, Kadek Nina; Ni Komang Aristya Julianingsih; Desak Ketut Rantris Priyatnis; Ni Wayan Rati; I Wayan Lasmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The importance of the integration between Content Standards and Graduate Competency Standards plays a crucial role in ensuring the quality of learning in schools. This study aims to describe the implementation of Content Standards and Graduate Competency Standards at SMP Negeri 1 Dawan. This research employed a qualitative approach with a descriptive design. Data were collected through interviews, observations, documentation studies, and literature reviews, and were analyzed through data reduction, data display, and conclusion drawing. The results indicate that the implementation of Content Standards has been carried out through the organization of intracurricular, co-curricular, extracurricular, local content, and inclusive programs. The implementation of Graduate Competency Standards is reflected in character development, the improvement of literacy and numeracy skills, as well as academic and non-academic evaluations. Both standards demonstrate a strong interrelationship in supporting the holistic development of students’ competencies. However, further optimization is still required through improving teacher competence, conducting periodic curriculum evaluations, and implementing differentiated learning.